Upaya Guru dalam Mengatasi Permasalahan Pembelajaran Al-Qur’an pada Anak Berkebutuhan Khusus (Studi pada Anak Tuna Grahita di SKh KORPRI Pandeglang) - Euis Ernawati; Ela Hikmah Hayati; Soviaturrohmah (CV. Creative Tugu Pena, 2024)
This research aims to describe teachers' efforts to overcome the problems of learning the Al-Qur'an for mentally retarded children. This research uses a qualitative method with a descriptive approach. The data collection in this research includes; interviews, observations, and documentation. This research was carried out at SKh KORPRI Pandeglang in 2022. The results of this research show that there are problems faced by mentally retarded children in reading the Al-Qur'an, namely; Their low IQ results in difficulty remembering and pronouncing the hijaiyah letters, and they easily forget when learning to read the Al-Qur'an. Meanwhile, teachers' efforts to improve the ability of mentally disabled children to read the Al-Qur'an are by using visual and audiovisual media as well as the iqra' (reading), imitating, repeating and memorizing methods. The supporting factors for teachers' efforts to improve the ability to read the Al-Qur'an are parents who play a role in the learning process of reading the Al-Qur'an at home, the presence of visual and audio-visual media in learning at school, then the activity of reading the Al-Qur'an This is not only done during IMTAK activities, but is also done every day before class starts. Meanwhile, the inhibiting factor is apart from the IQ of mentally retarded children which is different from other children of the same age, but also the pronunciation of the Al-Qur'an which is less clear. With the efforts and strategies made by teachers, as well as cooperation between children and parents, it can facilitate the process of learning the Al-Qur'an for children with mental disabilities.